Magnetic Activity of Pre-main Sequence Stars near the Stellar-Substellar Boundary. Issue Volume 10:Issue S314(2015) (November 2015) - Principe, David; Kastner, Joel. H.; Rodriguez, David
Abstract: X-ray observations of pre-main sequence (pre-MS) stars of M-type probe coronal emission and offer a means to investigate magnetic activity at the stellar-substellar boundary. Recent observations of main sequence (MS) stars at this boundary display a decrease in fractional X-ray luminosity ( L X / L bol ) by almost two orders of magnitude for spectral types M7 and later. We investigate magnetic activity and search for a decrease in X-ray emission in the pre-MS progenitors of these MS stars. We present XMM-Newton X-ray observations and preliminary results for 10 nearby (30-70 pc), very low mass pre-MS stars in the relatively unexplored age range of 10-30 Myr. We compare the fractional X-ray luminosities of these 10-30 Myr old stars to younger (1-3 Myr) pre-MS brown dwarfs and find no dependence on spectral type or age suggesting that X-ray activity declines at an age later than 30 Myr in these very low-mass stars.